2016
DOI: 10.1039/c6ra18210k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and catalytic activity of ruthenium indenylidene complexes bearing unsymmetrical NHC containing a heteroaromatic moiety

Abstract: New ruthenium(ii) indenylidene catalysts were synthesized and used in olefin metathesis reactions in toluene under air, leading to high conversions and good selectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Selected indenylidene (Ru47-50) and Hoveyda-type (Ru51-54) catalysts bearing N-(heteroaryl)methylene uNHC ligands. [51][52] ethenolysis process catalyzed by this complex, a reaction of technical 27 with grade 3.0 ethylene was attempted at 1 L scale using 150 ppm of catalyst, leading to 56 % of conversion and selectivity of 97 %. 53a While these results are of interest in the context of high selectivity, it shall be noted that with a modern CAAC-based catalyst, in similar 1-L scale technicalgrade ethenolysis, we were able to obtain comparable conversion with a catalyst loading as low as 50 ppm.…”
Section: A Versatile Thiophene-based Unhc Ru Catalystmentioning
confidence: 99%
“…Selected indenylidene (Ru47-50) and Hoveyda-type (Ru51-54) catalysts bearing N-(heteroaryl)methylene uNHC ligands. [51][52] ethenolysis process catalyzed by this complex, a reaction of technical 27 with grade 3.0 ethylene was attempted at 1 L scale using 150 ppm of catalyst, leading to 56 % of conversion and selectivity of 97 %. 53a While these results are of interest in the context of high selectivity, it shall be noted that with a modern CAAC-based catalyst, in similar 1-L scale technicalgrade ethenolysis, we were able to obtain comparable conversion with a catalyst loading as low as 50 ppm.…”
Section: A Versatile Thiophene-based Unhc Ru Catalystmentioning
confidence: 99%
“…These proved useful as olefin‐metathesis precatalysts, not only, in standard conditions under an argon atmosphere, but also in commercial grade nondegassed solvents (Figure , L10‐B ) . Importantly, those complexes were successfully applied in the ethenolysis of ethyl oleate (Figure , L12‐B , C ) and afforded low isomerization in self‐metathesis of α‐olefins (Figure , L11‐C ) . They were also used in reactions with 1 ppm pre‐catalyst loading yielding 232 735 TON (Figure , L14‐B ) .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies on benzyl‐substituted uNHC (e.g., L2 ), we found that an increase of the steric bulk of the N ‐aromatic substituent, by replacing Mes with DIPP, brought promising enhanced selectivity to the catalysts derived from such altered ligands, however at the cost of slightly diminished activity ,. In the present work, we decided to focus on the not yet fully explored class of uNHC ligands that bear a heterocyclic N ‐substituent in their structure ,,. We opted to check if modification of the thiophene‐based uNHC ligand can lead to a catalyst of higher selectivity, which is at the same time easy to handle, tolerant to diverse functional groups, and sufficiently active to be applied in more polar (green) solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The class of ruthenium indenylidene precatalysts with symmetrical NHC carbenes ( 2 a – c ) has been extensively studied . In contrast, ruthenium indenylidene complexes bearing unsymmetrical NHC carbene subunits are largely unexplored ,,,…”
Section: Introductionmentioning
confidence: 99%